Cut-off Values of Bacteriuria and Leukocyturia for the Diagnosis of Urinary Tract Infections in Pediatric Patients - Muhamad Ramdani Ibnu Taufik; Dian Ariningrum; Yusuf Ari Mashuri (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
The diagnosis of Urinary Tract Infection (UTI) in infants and children is often missed. There have been no studies ondiagnostic tests using automated urine analyzer in pediatric patients. This study aimed to determine the cut-off values ofbacteriuria and leukocyturia using the automated urine analyzer Sysmex UX-2000 to diagnose UTI with the gold standard ofautomated urine culture using VITEK 2 in pediatric patients at Dr. Moewardi Hospital, Surakarta. An observational analyticalstudy with the cross-sectional design was during August-October 2019 at the Clinical Pathology Laboratory and ClinicalMicrobiology Laboratory of Moewardi Hospital, Surakarta. Eighty-four patients sample were collected. This study'sdependent variable was the diagnosis of urinary tract infections in pediatric patients established with positive culture results(bacterial count of ≥ 105 CFU/mL urine). This study's independent variables were the number of urine bacteria (BACT) andthe number of urine leukocytes (WBC) from urinalysis using the Sysmex UX-2000 automated urine analyzer. A diagnostictest was used for data analysis. The best cut-off value for leukocyturia was 37 cells/μL with a 61.1% sensitivity, 63.6%specificity, a positive predictive value of 31.4%; a negative predictive value of 85.7; positive likelihood ratio of 1.64; negativelikelihood ratio of 0.595, and accuracy of 63%. The best cut-off for the number of bacteria was 143 cells/μL with a sensitivityof 66.7%; specificity of 71.2%, the positive predictive value of 38.7%, the negative predictive value of 88.7%; positivelikelihood ratio of 2.14; negative likelihood ratio of 0.432 and an accuracy of 70.2%. A cut-off of 37 cells/μL for leukocyturiaand 143 cells/μL for bacteriuria using an automated urine analyzer can be used for UTI screening in pediatric patients.